2015
DOI: 10.1016/j.athoracsur.2015.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury and Hemodilution During Cardiopulmonary Bypass: A Changing Scenario

Abstract: A bundle of interventions mainly aimed at limiting the renal impact of hemodilution during CPB is effective in reducing the AKI rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 23 publications
3
55
0
2
Order By: Relevance
“…Hemodilution during CPB is an independent risk factor for AKI in adult cardiac surgery, with improved outcomes for cases in which significant hemodilution (hematocrit <24%) is avoided during CPB . Although lower hemoglobin (8.8 versus 13.1 g/dL) preoperatively and on arrival to the intensive care unit has been associated with persistent AKI after cardiac surgery, transfusion of at least 2 U of packed red blood cells has also been associated with higher incidence of CVS‐AKI .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemodilution during CPB is an independent risk factor for AKI in adult cardiac surgery, with improved outcomes for cases in which significant hemodilution (hematocrit <24%) is avoided during CPB . Although lower hemoglobin (8.8 versus 13.1 g/dL) preoperatively and on arrival to the intensive care unit has been associated with persistent AKI after cardiac surgery, transfusion of at least 2 U of packed red blood cells has also been associated with higher incidence of CVS‐AKI .…”
Section: Resultsmentioning
confidence: 99%
“…187,188 Hemodilution during CPB is an independent risk factor for AKI in adult cardiac surgery, 189 with improved outcomes for cases in which significant hemodilution (hematocrit <24%) is avoided during CPB. 190 Although lower hemoglobin (8.8 versus 13.1 g/dL) preoperatively and on arrival to the intensive care unit has been associated with persistent AKI after cardiac surgery, 191 transfusion of at least 2 U of packed red blood cells has also been associated with higher incidence of CVS-AKI. 192 In 2 recent RCTs in which patients were randomized to a liberal (Hg <9.5 g/dL) or restrictive (Hg <7.5 g/dL) transfusion policy intraoperatively and postoperatively, there was no difference in postoperative outcomes including AKI.…”
Section: Nonpharmacological Strategiesmentioning
confidence: 99%
“…Many improvements to CPB technology have been introduced over the past decade to limit the risk associated with haemodilution with a focus on redesign of the circuit to reduce volume, the use of retrograde autologous priming and management of intraoperative fluid administration. Observational studies have suggested some improvement in the incidence of AKI following such changes …”
Section: Risk Factors For Cardiac Surgery‐associated Acute Kidney Injurymentioning
confidence: 99%
“…Observational studies have suggested some improvement in the incidence of AKI following such changes. 45…”
Section: Haematocrit and Acute Kidney Injurymentioning
confidence: 99%
“…Furthermore, it would have been of interest to know the threshold for packed red blood cells transfusion to ensure an adequate oxygen delivery, a wellknown key factor to prevent postoperative AKI. 2,8 To date, we have many reliable tools to predict the risk of AKI through the combination of clinical parameters and biological markers but not powerful strategies to prevent it. Techniques aimed at maximizing renal perfusion are promising, even if there is no evidence that they prevent all AKI stages.…”
mentioning
confidence: 99%